Organoleptic and Hedonic Tests On Soft Candy Formulations From Essential Oil Active Ingredients Fennel Seeds (Foeniculum Vulgare) - Ag. Kirwanto; Susilo Y; Ronal T (CV. ULIL ALBAB CORP, 2025)
One of the plants in Indonesia that is beneficial for health is fennel ( Foeniculum vulgare ). Fennel has long been known as a component of traditional medicine. The plant has been commercially cultivated for its oil. Fennel oil is known to have a strong effect on the digestive system as an appetite stimulant, increasing gastric secretion and bile content, having a carminative effect, and as an expectorant. All levels of society of all ages are very fond of candy. One type of candy that is widely circulated today is soft candy . Making soft candy from the active ingredient of fennel seed essential oil can be useful for overcoming health problems in a more practical and economical way. The purpose of this study was to determine the results of organoleptic and hedonic tests on the formulation of soft candy from the active ingredient of fennel seed essential oil ( Foeniculum vulgare ). The research method used was observational with a descriptive research design. The population used were students living in the Midwifery Department Dormitory of the Ministry of Health Polytechnic of Surakarta. The sampling technique was simple random sampling with a sample of 55 students. The research instrument used was a questionnaire. The ready-to-eat soft candy formula has a chewy texture, pale orange color, orange aroma, and sweet taste with a distinctive fennel seed flavor. Most respondents disliked it.